Ethics in real estate: agency practices in Istanbul - Markoc, Ilkim; Cizmeci, Fusun (EMERALD GROUP PUBLISHING LTD, 2021)
Purpose This paper aims to discuss unethical behaviors that small real estate agencies encounter in real estate brokerage practices, the factors that give rise to a trust issue and the potential of legal arrangements for offering a solution. Small real estate agencies, almost the only actor in the real estate brokerage industry until the late twentieth century, still strive to survive despite the globalized market, large corporations increasingly dominating the market, the increasing informality and the real estate portals offering certain brokerage services online. While all these developments put pressure on small real estate agencies, the industry's unethical behaviors diminish their reliability. Despite the efforts to overcome this issue through legal arrangements, the extent to which these regulations will be successful is still a matter of intense debate. Design/methodology/approach In total, 85 small real estate agencies operating in Istanbul, Turkey, were posed semi-structured open-ended questions and asked to provide an opinion about the unethical behaviors they face and the potential of a legal arrangement to solve those problems. In the second stage, three focus group interviews were held with representatives from large real estate brokerage companies to make a comparison and they were also posed similar questions. The answers were evaluated using content analysis. Findings It was found that the unethical behaviors in the real estate industry could mainly be evaluated in two categories, i.e. those stemming from structural problems of the industry and those stemming from problems related to service delivery and that a legal arrangement could only solve the first category. Research limitations/implications The research is limited to small real estate agencies that operate in Istanbul, the heart of the Turkish economy and the biggest city of the country where intensive efforts are spent to integrate into the global order. Originality/value It is considered that categorization of the causes of problems encountered by the numerous small real estate agencies that struggle to survive in the market and an analysis of the root causes of unethical behaviors in the industry and a discussion on potential solutions that may be brought bylaws will contribute to the literature.
Keywords: Informality; Istanbul; Ethics; Property marketing; Real estate practices; Real estate agent; Urban Studies